Determination of an optimally sensitive and specific chemical exchange saturation transfer MRI quantification metric in relevant biological phantoms. (30th September 2016) - Ray, Kevin J.; Larkin, James R.; Tee, Yee K.; Khrapitchev, Alexandre A.; Karunanithy, Gogulan; Barber, Michael; Baldwin, Andrew J.; Chappell, Michael A.; Sibson, Nicola R.
Abstract : The purpose of this study was to develop realistic phantom models of the intracellular environment of metastatic breast tumour and naïve brain, and using these models determine an analysis metric for quantification of CEST MRI data that is sensitive to only labile proton exchange rate and concentration. The ability of the optimal metric to quantify pH differences in the phantoms was also evaluated. Novel phantom models were produced, by adding perchloric acid extracts of either metastatic mouse breast carcinoma cells or healthy mouse brain to bovine serum albumin. The phantom model was validated using 1 H NMR spectroscopy, then utilized to determine the sensitivity of CEST MRI to changes in pH, labile proton concentration, T 1 time and T 2 time; six different CEST MRI analysis metrics (MTRasym, APT*, MTRRex, AREX and CESTR* with and without T 1 / T 2 compensation) were compared. The new phantom models were highly representative of the in vivo intracellular environment of both tumour and brain tissue. Of the analysis methods compared, CESTR* with T 1 and T 2 time compensation was optimally specific to changes in the CEST effect (i.e. minimal contamination from T 1 or T 2 variation). In phantoms with identical protein concentrations, pH differences between phantoms could be quantified with a mean accuracy of 0.6 pH units. We propose that CESTR* with T 1 and T 2 time compensation is the optimal analysis method for these phantoms. Analysis of CEST MRI data with T 1 / T 2 time compensated CESTR* is reproducible between phantoms, and its application in vivo may resolve the intracellular alkalosis associated with breast cancer brain metastases without the need for exogenous contrast agents. Abstract : Novel biologically relevant phantom models of the intracellular environment of metastatic breast tumour and naïve brain were produced, and used to determine an optimally sensitive and specific analysis metric for quantification of pH from CEST MRI data. Of the analysis methods compared, CESTR* with T 1 and T 2 time compensation was optimally specific to changes in the CEST effect (i.e. minimal contamination from T 1 or T 2 variation), with the ability to measure quantitative differences in pH with an accuracy of 0.6 pH units.